Antenna arrays a computational approach - Haupt, Randy L. (Hoboken, N.J. Wiley/IEEE Press, 2010)
This book covers a wide range of antenna array topics that are becoming increasingly important in wireless applications, particularly in design and computer modeling. Signal processing and numerical modeling algorithms are explored, and MATLAB computer codes are provided for many of the design examples. Pictures of antenna arrays and components provided by industry and government sources are presented with explanations of how they work. Antenna Arrays is a valuable reference for practicing engineers and scientists in wireless communications, radar, and remote sensing, and an excellent textbook for advanced antenna courses.
Keywords: Antenna arrays -- Mathematical models